2010
DOI: 10.1111/j.1399-3062.2010.00497.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and prognosis of invasive fungal infections in allogeneic stem cell transplantation recipients: a single-institution experience

Abstract: Post-transplant IFI was an unfavorable prognostic factor of the SCT recipients, and risk stratification can identify patients with high risk of IFI. Use of steroid played an important role in the pathogenesis as well as prognosis of IFI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…24 Concerning the univariate analysis of prognostic factors, our findings were consistent with other studies showing that corticosteroid dosage, aGVHD, cGVHD and CMV infection could increase the risk of post-engraftment or late IFD. 1,5 In addition, we found that post-engraftment IFD was associated with several risk factors that have been previously related with early or overall IFD, such as older age, delayed neutrophil engraftment, previous SCT, HLA mismatch and non PBSCT. 3,4 Our data suggest that ATG-containing regimens could increase the risk of IFD, which is in line with other studies reporting ex vivo T-cell depletion using Cl of IFD alemtuzumab as a risk factor for IFD.…”
Section: Site Of Infectionmentioning
confidence: 57%
See 3 more Smart Citations
“…24 Concerning the univariate analysis of prognostic factors, our findings were consistent with other studies showing that corticosteroid dosage, aGVHD, cGVHD and CMV infection could increase the risk of post-engraftment or late IFD. 1,5 In addition, we found that post-engraftment IFD was associated with several risk factors that have been previously related with early or overall IFD, such as older age, delayed neutrophil engraftment, previous SCT, HLA mismatch and non PBSCT. 3,4 Our data suggest that ATG-containing regimens could increase the risk of IFD, which is in line with other studies reporting ex vivo T-cell depletion using Cl of IFD alemtuzumab as a risk factor for IFD.…”
Section: Site Of Infectionmentioning
confidence: 57%
“…(4 patients), A. fumigatus (3), A. flavus (1) and Criptococcus spp. (1). The NRM at 6 and 12 months among patients who developed IFD was 12 and 40%, respectively, while patients without IFD had 9 and 16%, respectively (P o0.0001).…”
Section: Primary Antifungal Prophylaxismentioning
confidence: 87%
See 2 more Smart Citations
“…In a multicenter trial evaluating the effect of high-dose dexamethasone versus low-dose dexamethasone in combination with lenalidomide for first-line myeloma treatment there was a significant increase in infectious complications for patients in the high-dose steroid group, underlining the influence of steroid dosage when added to another potentially immunosuppressive therapeutic regimen [28]. Especially for opportunistic infectious pathogens like Aspergillus spp., high dose steroids are a major independent factor for invasive aspergillosis and also confer an inferior prognosis in hematologic patients after allogeneic transplantation [29]. Furthermore, they are an independent risk factor for IA even for otherwise non-immunocompromised patients [30]: In a recent analysis [31] the majority of hematologic patients treated with rituximab with Pneumocystis jirovecii pneumonia had high-dose glucocorticoid exposure, underlining the pronounced effect of steroid co-medication in the pathogenesis of opportunistic infections.…”
Section: Discussionmentioning
confidence: 99%